Cyberspace Safety and Security: 13th International Symposium, CSS 2021, Virtual Event, November 9-11, 2021, Proceedings - Meng, Weizhi; Conti, Mauro (Lecture Notes in Computer Science, 2022)
The LNCS 13172  constitute the proceedings of the 13th International Symposium on Cyberspace Safety and Security, CSS 2021, held online, in November 2021.The 9 full papers and 5 short papers presented in this book were carefully reviewed and selected from 35 submissions. The conference focuses on Cyberspace Safety and Security, such as authentication, access control, availability, integrity, privacy, confidentiality, dependability and sustainability issues of cyberspace.